Optimal Ownership and Firm Performance: An Analysis of China’s FDI Liberalization - Eppinger, Peter; Ma, Hong (The Review of Economics and Statistics, 2026)
Seminal theories of the firm posit that firm ownership is allocated to minimize contractual inefficiencies. Yet, it remains unclear how much the optimal ownership choice affects firm performance in practice. This paper provides a first quantification of the gains from optimal ownership within multinational firms by exploiting a major liberalization of China’s policy restrictions on foreign ownership. The liberalization allowed previously restricted firms to become fully foreign-owned. We find that these reoptimized ownership choices raise firm output by 40% and productivity by 7.5% on average. An extended property-rights theory of the multinational firm rationalizes these effects and their heterogeneity.